Design of a 360-deg panoramic capture system based on a smart phone - Song, Weitao (2020)
A panoramic imaging system has been developed using two afocal lenses and a smart phone that consists of cameras on both sides. An individual afocal lens has been developed with a large field of view (FOV) and a large exit pupil, which can enlarge the FOV of a smart phone camera to above 180 deg. Some issues with the smart phone-based 360-deg panoramic system, such as relative illuminance and assembly tolerance, were analyzed in detail and taken into consideration during the design procedure. A prototype has been developed with a low fabrication cost, yet producing impressive panoramic image quality.